2017
DOI: 10.1016/j.cya.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of information quality due accounting regulatory changes: Applied case to Mexican real sector

Abstract: The purpose of this paper is to examine whether changes in accounting standards improve value relevance of financial information on listed companies in Mexico. The research was conducted for the period 2000-2013 using a sample of 141 companies that report to the Mexican stock exchange using the methodology of panel data. Our findings show that changes in local regulations (generally accepted accounting principles) to internationally approved standards (Financial Reporting Standards and International Financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
1
4
0
1
Order By: Relevance
“…It can be concluded that the human resources quality variable has a positive significant effect on the user satisfaction of Accrual-Based Accounting System of Institutions application. The results of this study are in line with the results of the research conducted by Mendoza et al, 2011;Cheuk et al, 2017;Iannacci and Comford, 2017;Zerbino et al 2017;Tam et al, 2017;Hernandez-Ortega et al, 2017;Sánchez et al, 2017;Almazán et al, 2017;Alzahrani, et al, 2017;Shin et al, 2017;Horvath andBauermeister, 2017 and. The operator of work unit is the most associated party with the operations of Accrual-Based Accounting System of Institutions application.…”
Section: The Effect Of Human Resources Quality On User Satisfactionsupporting
confidence: 88%
See 3 more Smart Citations
“…It can be concluded that the human resources quality variable has a positive significant effect on the user satisfaction of Accrual-Based Accounting System of Institutions application. The results of this study are in line with the results of the research conducted by Mendoza et al, 2011;Cheuk et al, 2017;Iannacci and Comford, 2017;Zerbino et al 2017;Tam et al, 2017;Hernandez-Ortega et al, 2017;Sánchez et al, 2017;Almazán et al, 2017;Alzahrani, et al, 2017;Shin et al, 2017;Horvath andBauermeister, 2017 and. The operator of work unit is the most associated party with the operations of Accrual-Based Accounting System of Institutions application.…”
Section: The Effect Of Human Resources Quality On User Satisfactionsupporting
confidence: 88%
“…Human resources (HR) are the people who are in an organization who contribute through their thoughts and perform various jobs in achieving the organizational goals. The contribution is the thought that they have in various activities within the organization Dharsuky, 2015, Mendoza et al, 2011;Cheuk et al, 2017;Iannacci and Comford, 2017;Achamad et al, 2017;Zerbino et al 2017;Tam et al, 2017;Hernandez-Ortega et al, 2017;Sánchez et al, 2017;Almazán et al, 2017;Alzahrani, et al, 2017;Shin et al, 2017;Horvath and Bauermeister, 2017;Pohan et al, 2018). The ability of the organization to deliver its goals is determined by the quality of human resources owned by the organization.…”
Section: Human Resources (Hr) Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…The mentioned research gives an affirmation that Sharia-obedient firms are under close examination from regulator compared to other firms. Furthermore, as shown by Sánchez, Alejandro, Sáenz, and García (2017), a higher accounting information quality can be achieved in a closely regulated environment, and it is evident that Sharia-obedient firms are eager to provide an honest accounting report for investors. Besides Malaysia, Indonesia is one of the targeted markets for Sharia-obedient financial markets in Southeast Asia (Pranata & Nurzanah, 2015).…”
Section: Introductionmentioning
confidence: 99%